2023
DOI: 10.1002/mc.23589
|View full text |Cite
|
Sign up to set email alerts
|

RAB6A functions as a critical modulator of the stem‐like subsets in cholangiocarcinoma

Abstract: RAB6A is a member of RAB GTPase family and plays an important role in the targeted transport of neurotrophic receptors and inflammatory cytokines. RAB6A‐mediated secretory pathway is involved in many physiological and pathological processes. Defects in RAB6A‐mediated secretory pathway may lead to the development of many diseases, including cancer. However, its role in cholangiocarcinoma (CCA) has not yet been revealed. We explored the regulatory role of RAB6A in the stem‐like subsets of CCA. We showed that RAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…On the other hand, previous studies indicated that lesser HLA-A expression levels in TNBC resulted in poor clinical outcomes and it acts as a tumor suppressor (Pujadas and Cordon-Cardo 2021). Moreover, higher level of RAB6A expression is correlated with tumor growth in different cancers (Yang et al 2023). Furthermore, we performed similar RFS analysis for the genes that commonly switched allelic expression between high biallelic and low biallelic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, previous studies indicated that lesser HLA-A expression levels in TNBC resulted in poor clinical outcomes and it acts as a tumor suppressor (Pujadas and Cordon-Cardo 2021). Moreover, higher level of RAB6A expression is correlated with tumor growth in different cancers (Yang et al 2023). Furthermore, we performed similar RFS analysis for the genes that commonly switched allelic expression between high biallelic and low biallelic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher level of RAB6A expression is correlated with tumor growth in different cancers (Yang et al 2023). Furthermore, we performed similar RFS analysis for the genes that commonly switched allelic expression between high biallelic and low biallelic cells.…”
Section: Discussionmentioning
confidence: 99%